DEVELOPING A KEY RISK DISCLOSURE QUALITY INDEX: A SCORING FRAMEWORK FOR MALAYSIAN PUBLIC-LISTED COMPANIES - Osman, Amir Hakim; Abdullah, Azrul; Mahmud, Nurfarizan Mazhani (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This paper develops a Key Risk Disclosure Quality (KRIS-DQ) Index to assess the quality of key risk disclosures in the annual reports of Malaysian public-listed companies. Drawing on Ibrahim and Hussainey’s (2019) three-step approach to disclosure index construction, the KRIS-DQ Index integrates content analysis principles with a structured five-level scoring scale that captures disclosure presence, specificity, mitigation strategies, and the use of quantitative information. The index covers 18 key risk categories identified from KPMG’s annual risk outlooks and is explicitly aligned with the Malaysian Code on Corporate Governance (MCCG) 2021 and Bursa Malaysia Listing Requirements, enabling structured evaluation of disclosure quality in relation to regulatory expectations. An illustrative application of the index demonstrates its ability to capture meaningful variation in disclosure quality across firms and risk categories, addressing key limitations of prior measures that focus predominantly on disclosure quantity rather than depth and decision usefulness. The KRIS-DQ Index provides a practical benchmarking and diagnostic tool for regulators, investors, and researchers, and offers a robust foundation for future empirical research on corporate risk disclosure quality in emerging market contexts, where institutional environments and enforcement variability heighten the need for more discriminating disclosure quality measures.